Efficacy of Vitamins B Supplementation on Mild Cognitive Impairment and Alzheimer’s Disease: A Systematic Review and Meta-Analysis - Li, Meng-Meng; Yu, Jin-Tai; Wang, Hui-Fu; Jiang, Teng; Wang, Jun; Meng, Xiang-Fei; Tan, Chen-Chen; Wang, Chong; Tan, Lan (Current Alzheimer Research, 2014)
Despite B vitamin supplementation playing an important role in cognitive function, the exact effect remains unknown. The aim of this study was to systematically review and quantitatively synthesize the efficacy of treatment with vitamins B supplementation in slowing the rate of cognitive, behavioral, functional and global decline in individuals with MCI or AD. A systematic literature search in PubMed, EMBASE, International Pharmaceutical Abstracts, clinicaltrials. gov, the Cochrane Controlled Trials Register, the Cochrane Database of Systematic Reviews, and the Cochrane Cognitive Improvement Group specialized registry was conducted on April 2014, with no limit of date. Five trials met the eligibility criteria and were selected for this meta-analysis. Meta-analysis showed moderate beneficial effects of vitamins B supplementation on memory (SMD 0.60, 95% CI 0.20, 1.00), whereas no significant difference on general cognitive function (WMD -0.10, 95% CI -0.80, 0.59), executive function (SMD 0.05, 95% CI -0.11, 0.21) and attention (WMD -0.03, 95% CI -1.20, 1.14) were found in MCI patients. In addition, no significantly cognitive benefits on the Alzheimer’s Disease Assessment Scale (ADAS-cog) (WMD 1.01, 95% CI -0.68, 2.70) and Mini Mental State Examination (MMSE) (WMD -0.22, 95% CI -1.00, 0.57), functional (SMD 0.13, 95% CI -0.05, 0.31), behavioral (SMD 0.04, 95% CI -0.16, 0.25) or global (WMD 0.07, 95% CI -0.48, 0.62) change were observed in AD patients. Collectively, weak evidence of benefits was observed for the domains of memory in patients with MCI. Nevertheless, future standard RCTs are still needed to determine whether it was still significant in larger populations. However, the data does not yet provide adequate evidence of an effect of vitamins B on general cognitive function, executive function and attention in people with MCI. Similarly, folic acid alone or vitamins B in combination are unable to stabilize or slow decline in cognition, function, behavior, and global change of AD patients.
Keywords: meta-analysis